(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
The levels of fatty acids, phospholipids and sterols were determined in the skin and muscle of Pellenula afzeliusi using gas chromatograph. Results showed crude fat varied from 0.697-7.476 g/100 g; SFA varied from 30.3-34.8 % of total fatty acids, total unsaturated fatty acids varied from 57.3-61.2 %, PUFA range was 12.1-17.8 % and PUFA/SFA ranged from 0.348-0.587. Both skin and muscle had high levels of n-6 fatty acids but low in n-3 fatty acids. The correlation coefficient was significantly and positively high at r = 0.05 in the fatty acids. In the phospholipids, cephalin was highest in skin but lecithin was highest in the muscle with respective values of 965 and 432 (mg/100 g). The sterol values in the skin varied between 111-112 (111.5±0.58) mg/100 g and muscle was 19.5-19.6 (19.6±0.058) mg/100 g. Whilst 100 g skin would provide 5.233 g fatty acids, 100 g muscle would provide 0.488 g fatty acids. Key words: Lipid profile; Skin and muscle; Pellenula afzeliusi; Gas chromatograph; Fatty acid; Phospholipid; Sterol DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9602 BJSIR 2011; 46(4): 523-532